Analysis of Polyamine Polymer and KCl Polymer Mud Properties in Brine at Various Temperatures - Meier, Carolyn Rose; Prapansya, Onnie Ridaliani; Husla, Ridha (Penerbitan Universitas Trisakti, 2024)
Drilling mud is an essential element in oil and gas well drilling operations. With primary functions such as lifting cuttings to the surface and maintaining borehole stability, it plays a vital role in ensuring a smooth and successful drilling process. The major challenge in drilling operations is dealing with reactive clay or shale formations that are susceptible to clay swelling and formation damage. To overcome this problem, high-performance water-based muds, such as KCl and Polyamine polymer muds, have been developed. Laboratory studies were conducted to test the physical properties of the muds at temperatures of 80 ˚F, 200 ˚F, and 250 ˚F for 16 hours using a hot roller. Tests included density, viscosity, rheology, and plastic viscosity. The mud composition was equalized at all temperatures to assess comparative performance. The results showed a decrease in the physical properties of polyamine polymer and KCl polymer muds with increasing temperature. To maintain the performance of the mud at high temperatures, additional treatment with additives were required. Barite, PAC LV, XCD, and PHPA were the additives introduced to the polymer KCl and polyamine mud in this experiment. It took 45 grams of barite in total to reach the necessary density requirements. For polyamine mud, 1.5 grams of PAC LV and for polymer KCl mud, 3.5 grams of PAC LV were needed to reach the necessary viscosity requirements. In the meantime, 1.5 grams of XCD and 2.5 grams of PHPA were needed to achieve the plastic viscosity requirements for polyamine mud, and 1 gram of XCD and 2 grams of PHPA were needed for polymer KCl mud.